Copper Induces Oxidative Stress and Apoptosis in the Mouse Liver. (11th January 2020) - Liu, Huan; Guo, Hongrui; Jian, Zhijie; Cui, Hengmin; Fang, Jing; Zuo, Zhicai; Deng, Junliang; Li, Yinglun; Wang, Xun; Zhao, Ling
Abstract : Copper (Cu) is an essential trace element involved in the normal physiological processes of animals. However, excessive exposure to Cu can produce numerous detrimental impacts. The aim of this study was to investigate the effects of Cu on oxidative stress and apoptosis as well as their relationship in the mouse liver. Four-week-old ICR mice (n = 240 ) were randomly assigned to different Cu (Cu2+-CuSO4) treatment groups (0, 4, 8, and 16 mg/kg) for periods of 21 and 42 days. The high doses of Cu exposure could induce oxidative stress, by increasing the levels of reactive oxygen species (ROS) and protein carbonyls (PC) and decreasing the activities of antisuperoxide anion (ASA) and antihydroxyl radical (AHR) and content of glutathione (GSH), as well as activities and mRNA expression levels of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px). Moreover, high doses of Cu exposure induced hepatic apoptosis via the mitochondrial apoptotic pathway, as characterized by the depolarization of mitochondrial membrane potential (MMP); significantly increased mRNA and protein expression levels of cytosolic cytochrome (Cyt c), apoptosis-inducing factor (AIF), endonuclease G (Endo G), apoptosis protease-activating factor-1 (Apaf-1), cleaved caspase-9, cleaved caspase-3, cleaved PARP, Bcl-2 antagonist killer (Bak), Bcl-2-associated X protein (Bax), and Bcl-2-interacting mediator of cell death (Bim); and decreased mRNA and protein expression levels of B-cell lymphoma-2 (Bcl-2) and Bcl-extra-large (Bcl-xL). Furthermore, the activation of the tumor necrosis factor receptor-1 (TNF-R1) signaling pathway was involved in Cu-induced apoptosis, as characterized by the significantly increased mRNA and protein expression levels of TNF-R1, Fas-associated death domain (FADD), TNFR-associated death domain (TRADD), and cleaved caspase-8. These results indicated that exposure to excess Cu could cause oxidative stress triggered by ROS overproduction and diminished antioxidant function, which in turn promoted hepatic apoptosis via mitochondrial apoptosis and that the TNF-R1 signaling pathway was also involved in the Cu-induced apoptosis.